Oil Price Fluctuation and Current Accounts: Exploring Mediation Effects for Oil Importing Nations - Bibi, Salma; Haq, Mirajul; Rashid, Abdul (International Journal of Energy Economics and Policy, 2021)
The study is an attempt to examine empirically the effects of oil price shock on current account imbalances. The analysis is carried out on the cross-country panel of 160 countries that are divided into three different groups base on their level of oil imports. The relationship between the oil price shock and current account imbalances is rigorously assessed using two different approaches. Firstly, the seemingly unrelated regression models are used to estimate the effects of oil price shock on current account imbalances with transmission channels namely trade, valuation, and wealth. Secondly, to examine the indirect effects of oil price shock three different mediator effects that direct, indirect, and total are estimated. The findings of the study reveal that for all three groups of countries the oil price shock pose a positive effect on the current account through the trade channel. Whereas, the current account of all three groups is negatively associated with oil price shock with the wealth channel. The valuation channel holds a mix results across country groups about the effect of oil price shock on the current account balances. In the case of low and major oil importer countries, oil price shock is negatively associated with the current account, whereas the current account of medium oil importer countries is improving with an increase in oil prices. The mediation analysis holds mix results across groups of countries. Keywords: Current-account imbalances; oil importing economies, seemingly unrelated regression; mediation effects JEL Classifications: F4; F41 DOI: https://doi.org/10.32479/ijeep.11044